The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1161/circulationaha.123.065561
|View full text |Cite
|
Sign up to set email alerts
|

Bag-Valve-Mask Ventilation and Survival From Out-of-Hospital Cardiac Arrest: A Multicenter Study

Ahamed H. Idris,
Elisabete Aramendi Ecenarro,
Brian Leroux
et al.

Abstract: Background: Few studies have measured ventilation during early cardiopulmonary resuscitation (CPR) before advanced airway placement. Resuscitation guidelines recommend pauses after every 30 chest compressions to deliver ventilations. The effectiveness of bag-valve-mask ventilation delivered during the pause in chest compressions is unknown. We sought to determine: (1) the incidence of lung inflation with bag-valve-mask ventilation during 30:2 CPR; and (2) the association of ventilation with outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This, in addition to increasing the total volume of air without affecting the compression variables, could have an impact on increasing the likelihood of survival and favourable neurological outcome. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in addition to increasing the total volume of air without affecting the compression variables, could have an impact on increasing the likelihood of survival and favourable neurological outcome. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Additionally, providing effective ventilations is not always easy, as there are numerous factors that can influence poor quality (lack of experience, pre-fatigue after a rescue, or prolonged CPR). 17 , 18 Increasing the number of ventilations without affecting the other elements of BLS may compensate, maintain, or increase the success rate of ventilations delivered in prolonged basic life support.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Regarding ventilation, areas of uncertainty persist, 3 due to the complex interactions between ventilation and circulation. 2 , 4 A recent study from Idris et al showed that bag valve mask ventilation was often ineffective before advanced airway placement, 5 while a protective ventilation strategy could be preferred to prevent hyperventilation after intubation. 6 Over the years, several CPR ventilation strategies and new medical devices have been proposed, some of them interacting directly with circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CCC trial ultimately concluded that continuous chest compressions did not provide significantly higher rates of survival or favorable neurologic function than standard 30:2 CPR, Idris and colleagues in this issue of Circulation demonstrate valuable dividends drawn from the trial’s ambitious methodology. 8 Returning to retained CCC monitor defibrillator data, the authors extracted thoracic bioimpedance signals incorporated into 2 of 3 commercially available monitor defibrillators used in the CCC trial. Using novel, validated technology, these changes in electrical resistance occurring as a victim’s chest expands and contracts during chest compressions can now be used to quantify both the frequency and the volume of ventilation.…”
mentioning
confidence: 99%